Psychologists and their theories for students - Krapp, Kristine M.; Gale Group (Detroit, Mich. Thomson Gale, 2005)
Perfect for research assignments in psychology, science and history, this one-stop source for in-depth coverage of major psychological theories and the people who developed them provides a unique approach to the study of psychological history as it pertains to analysis. 2 volumes.
v. 1. A-K -- v. 2. L-Z.
Electronic reproduction.
Keywords: Psychologists; Psychology; Electronic books